Concrete Road Development: Financiers' and Environmental Perspectives in Sidoarjo District: Pembangunan Jalan Beton Pemerintah Kabupaten Sidoarjo: Perspektif Pembiaya dan Lingkungan - Fajar Muharram (Universitas Muhammadiyah Sidoarjo, 2023)
Development planning in developing countries still has a major role as a tool to encourage and control the development process more quickly and purposefully. The 2005-2024 RPJP states that one of the development missions is to realize a beautiful and sustainable Indonesia, and infrastructure development will lead to the concept of improving services for improving environmental quality in the future. In supporting economic and social activities in Sidoarjo Regency, it is necessary to improve good infrastructure facilities. The Sidoarjo district government made a policy for how access roads between villages and sub-districts are made with concrete road patterns. Concrete roads connecting villages and sub-districts can facilitate the flow of goods and people (increase mobility) by implementing efficient patterns of distribution services that can reach growth nodes. In this study using a qualitative research approach, with data analysis methods used to answer the first and second objectives used qualitative descriptive analysis. Highlights: Improved infrastructure: The concrete road development policy aims to enhance access between villages and sub-districts, facilitating the flow of goods and people, and improving mobility. Financial perspectives: The study explores the views of financiers regarding the concrete road development policy and its implications for funding and investment. Environmental considerations: The research investigates the environmental impacts of the concrete road development policy, focusing on sustainability and the concept of improving environmental quality in the region's future development. Keywords: Sidoarjo district government, concrete road development, financiers, environment, qualitative research.